A facile one-step synthesis of super-hydrophilic (NH4)0.33WO3/WS2 composites: a highly efficient adsorbent for methylene blue. (10th June 2020) - Zhang, Shuai; Yang, Ying; Xu, Lishuang; Yu, Hui; Li, Dan; Wang, Xinlu; Dong, Xiangting
Abstract : Super-hydrophilic ATBDs-3 composites synthesized using a hydrothermal method only needed less than 2 min to attain more than 80% of the MAC (80.45 mg g −1 ). Abstract : Super-hydrophilic ammonium tungsten bronze/tungsten disulfide composites ((NH4 )0.33 WO3 /WS2, ATBDs) were synthesized successfully using a one step hydrothermal method. They have super-hydrophilic properties, and the contact angle is 0 degree. (NH4 )0.33 WO3 /WS2 composites showed the morphology of nanorods with a diameter of approximately 50 nm and a length of a few microns. Less than 2 min was required to attain more than 80% of the maximum adsorption capacity (MAC, 80.45 mg g −1 ) and 10 min was required to attain 95% of the MAC in methylene blue aqueous solution. η (adsorption capacity in unit time, mg (g min) −1 ) was defined to further describe the adsorption capacity of the adsorbent. A high η value represents a high quality adsorption behavior, and the adsorbent has a η value of up to 8.045. The special structure, strong electrostatic interactions and super-hydrophilic properties lead to the high adsorption quality of ATBDs toward methylene blue.